Medical communication skills training in the Indian setting: Need of the hour - Chatterjee Sanjoy; Choudhury Nandita (Asian Journal of Transfusion Science, 2011)
Advances in science and technology have revolutionized medical services in the last two decades. Medical education in the undergraduate and postgraduate courses has tried to keep pace with the changes and several curriculum modifications have taken effect. One of the commonly seen changes include active participation in "communication skills" training and implementation of the same in practice. This article discusses the practical issues one would face in day-to-day medical communication and highlights the necessity of the same in the Indian setting, with a focus on transfusion medicine.